Medium-term results of surgical intervention on brachiocephalic and coronary arteries in patients with multifocal atherosclerosis - V. Beleyovych; A. Gabrielyan; A. Ratushnyuk; O. Beregovoy; I. Kudlai; S. Romanova (Ukrainian Journal of Cardiovascular Surgery, 2018)
Atherosclerosis is a systemic degenerative process that affects the aorta and the great vessels of the brain, heart and other organs. The analysis of the results of surgical treatment of patients with occlusive-stenotic lesion of two vascular pools, heart and brain in the medium-term follow-up period is insufficiently highlighted in the literature.The purpose of the work. To carry out a comparative analysis of the medium-term results of surgical treatment of patients with combined atherosclerotic lesions of the coronary and brachiocephalic arteries.Materials and methods. The analysis of medium-term results of surgical treatment of 62 patients with combined atherosclerotic occlusive-stenotic lesion of carotid and coronary arteries was carried out. The research protocol included general clinical and special methods: ECG, echocardiography, coronaro-ventriculography, duplex ultrasound scanning of the carotid arteries, perfusion computed tomography of the brain.Results and discussion. The result of surgical intervention and patient QoL of the first and second study groups in terms of up to 6 months were evaluated from the cardiological point of view, as good in 53 cases (94.6%), and as satisfactory in 3 cases (5.4%). There were no evidence of myocardial ischemia and recurrent myocardial infarction. Neurological status was assessed as good in 49 cases (87.5%), as satisfactory – in 6 cases (10.7%) and unsatisfactory – in 1 case (1.8%), where the cause was cerebral stroke. There were no statistically significant differences in the results of surgical treatment in the groups of single-stage intervention and stepped therapy. The negative dynamics of the clinical state over time was due mainly to the progression of the underlying disease.Conclusions. The analysis of the results of single-stage intervention and stepped therapy in patients with occlusive-stenotic lesion of two vascular pools established that the tactic of choosing the method of surgical correction of combined lesions of the coronary and brachiocephalic arteries developed by us allows us to obtain good results in the medium-term follow-up period. Angina pectoris and recurrent myocardial infarction at 6 months after surgery were not recorded. Only in 1 patient of the second group, that received stepped therapy on the coronary and brachiocephalic arteries, had acute nonfatal cerebral circulatory disorders. Thus, the choice of the optimal approach to the tactics of the operative intervention allows to safely performing the restoration of blood flow in patients with combined lesions of the carotid and coronary arteries.